Magnetic effect on the phase properties of neodymium-activated yttrium disilicate nanomaterials - BOYRAZ, CİHAT; ERDEM, MURAT (SCIENTIFIC TECHNICAL RESEARCH COUNCIL TURKEY-TUBITAK, 2016)
Under varying temperature conditions, undoped Y2Si2O7 and neodymium-doped Y2Si2O7 nanopowders were synthesized by the sol-gel method. The phase transitions from alpha to delta were observed in neodymium nanopowders by XRD measurements. TEM images showed ball-shaped structure forms for synthesized samples. The elemental compositions of all samples were established and quite close stoichiometry to all compound formulas was found using an attached component for TEM. To reveal the Nd dopant effect in different-phased Y2Si2O7 nanopowders, diffuse reflectance measurements were conducted. To establish the magnetic properties of undoped Y2Si2O7 and neodymium doped Y2Si2O7 nanopowders, an extensive study was carried out including M-H, M-2-H/M (Arrott's plot), and M-T under varying physical conditions. In the alpha phase, a significant paramagnetic increase was observed and a decrease in paramagnetic behavior was monitored by the effects of Nd dopant and increased annealing temperature.
Keywords: Yttrium silicate; sol-gel; phase transition; Nd-doped yttrium silicate; magnetic materials; WHITE-LIGHT EMISSION; PRESSURE; Y2SI2O7; ER3+; YB3+